Fracture Behavior of Nanoscale Notched Silicon Beams Investigated by the Theory of Critical Distances. Issue 1 (18th December 2017) - Gallo, Pasquale; Yan, Yabin; Sumigawa, Takashi; Kitamura, Takayuki
Abstract: This paper investigates the nanoscale fracture behavior of silicon using the Theory of Critical Distances (TCD) and demonstrates that TCD can correctly estimate the magnitude of the breakdown of continuum fracture mechanics. Moreover, it proposes the TCD as an alternative strategy for the determination of fracture toughness, K IC, at the nanoscale. More specifically, in situ micromechanical testing of notched nano‐cantilever beams has been carried out in a transmission electron microscope. The material characteristic length and fracture toughness are then evaluated. The average K IC value obtained is 0.98 MPa m 0.5, which is in agreement with that reported in the literature for macro‐Si. The characteristic length L is in the range of 1.3–1.9 nm. It is found that within an atomistic interpretation of the fracture of silicon, these values are in agreement with the breakdown of continuum fracture mechanics. Abstract : Nanoscale fracture behavior of single crystal silicon is investigated using the Theory of Critical Distances (TCD). Micromechanical testing of notched nano‐cantilever beams is carried out in a transmission electron microscope. It is demonstrated that the fracture toughness of Si is independent of the scale considered. Moreover, the breakdown of continuum fracture mechanics is correctly estimated.